2021
DOI: 10.1177/1753495x211028779
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following biosimilar TNF inhibitor use for inflammatory-mediated immune disorders in pregnancy

Abstract: Background Biosimilar tumour necrosis factor inhibitors (TNFi) are increasingly used to treat inflammatory immune-mediated disorders as they cost less than the originator biologic drug. More women are therefore becoming pregnant on biosimilar TNFi. This is the first paper to explore the safety and efficacy of biosimilar therapies in pregnancy. Methods A retrospective review of clinical data reviewed pregnancy outcomes and inflammatory disease activity in 18 pregnancies where the mother was using a biosimilar T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In conclusion, no new safety or efficacy issues arose from the use of IFXb or ETAb during conception, pregnancy or breastfeeding. Our data are reassuring and in line with studies of originator and biosimilar TNFi [ 6–8 ]. Patients under biosimilar TNFi should continue their usual therapy during conception and pregnancy to reduce the risk of flares and APO.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, no new safety or efficacy issues arose from the use of IFXb or ETAb during conception, pregnancy or breastfeeding. Our data are reassuring and in line with studies of originator and biosimilar TNFi [ 6–8 ]. Patients under biosimilar TNFi should continue their usual therapy during conception and pregnancy to reduce the risk of flares and APO.…”
supporting
confidence: 88%
“…There is scarce data about their use in pregnancy and for this reason, they are not addressed in the latest guidelines on reproductive health for rheumatic patients. To date, there is only one observational retrospective study describing the outcomes of pregnant women exposed to biosimilar TNFi, with the diagnoses of not only rheumatic conditions ( N = 9) but also inflammatory bowel disease ( N = 9) [ 6 ].…”
mentioning
confidence: 99%
“…Pregnancy outcomes and neonatal conditions were also captured. At each time point during pregnancy, patients were asked to compile questionnaires regarding the quality of life (QoL) and the assessment of their health by means of EuroQoL instrument EQ-5D-3L (−1.6: poorest QoL; 1: excellent QoL) 12 and Patient Global Health - Visual Analogic Scale (0–100; 0 poorest health – 100 full health), 13 respectively. During each of the two visits after delivery, the Edinburgh Postnatal Depression Scale (EPDS) 14 15 was administered to the patients; the same questionnaire was also proposed via a web-link at 12 months after delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Although many clinicians continue TNFi biosimilars in pregnancy, assuming they will behave the same as the parent drug, there are few studies examining this. Scott et al have reported a series of 18 women exposed to a TNFi biosimilar drug preconception and in pregnancy [150]. Seven women continued their biosimilar throughout pregnancy, 11 stopped their biosimilar therapy in pregnancy (2 in 1 st trimester, 8 in 2 nd trimester and 1 in 3 rd trimester).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%